Catatan atas gagalnya politik Orde Baru - Fatah, R. Eep Saefulloh, 1967- (Yogyakarta : Pustaka Pelajar, 1998)
Indonesian politics in the New Order era; collected articles.
Includes bibliographical references (p. xlvii-lvii) and index.
Keywords: Indonesia -- Politics and government -- 1966-1998.